Brain function effects of autonomous sensory meridian response (ASMR) video viewing - Sakurai, Noriko; Nagasaka, Kazuaki; Takahashi, Shingo; Kasai, Satoshi; Onishi, Hideaki; Kodama, Naoki (Frontiers in Neuroscience, 2023)
Abstract Background Autonomous Sensory Meridian Response (ASMR) is the sensation of tingling from audiovisual stimuli that leads to positive emotions. ASMR is used among young people to relax, induce sleep, reduce stress, and alleviate anxiety. Auditory stimulation in ASMR is thought to play the most important role among its triggers, and previous studies have used a mixture of auditory and visual stimulation and auditory stimulation. This is the first study to elucidate the difference in effects between direct auditory and visual stimulation and auditory stimulation from brain function using functional magnetic resonance imaging (fMRI). Methods The subjects were 30 healthy subjects over 19 years old. Brain function was imaged by fMRI while watching ASMR videos or listening to the sound files only. We administered a questionnaire based on a Likert scale determine if the participants felt a “relaxed mood” and “tingling mood” during the task. Results Significant activation was found in the visual cortex for audiovisual stimulation and in the visual and auditory cortex for auditory stimulation. In addition, activation of characteristic sites was observed. The specific sites of activation for audiovisual stimulation were the middle frontal gyrus and the left nucleus accumbens, while the specific sites of activation for auditory stimulation were the bilateral insular cortices. The questionnaire showed no significant differences in either “relaxed mood” or “tingling mood” in response to auditory and visual stimulation or auditory stimulation alone. Conclusions The audiovisual stimulation from ASMR involved the mesolimbic dopamine circuitry and suggested that it produced positive emotions. The auditory stimulation alone elicited bilateral insular cortex activation and suggested that the sympathetic balance was regulated. There was no difference in the mood of the participants, but the audiovisual stimulation was expected to have a more direct positive emotional effect. Although watching ASMR videos is more effective, the results suggest that listening to sound files only is useful for relaxation effects as appropriate for the time and place.